1990
DOI: 10.1037/0022-3514.58.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Individual-group discontinuity as a function of fear and greed.

Abstract: Two studies tested the schema-based distrust interpretation of the tendency of intergroup relations to be more noncooperative (or competitive) than interindividual relations. According to this interpretation, anticipated competitiveness rationally leads to noncooperativeness or defensive withdrawal. Thus, the postulated motivation is fear of the other group's competitive intent. Study 1 was a nonexperimental investigation in which discussion of distrust of another group was assessed and correlated with the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
178
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(187 citation statements)
references
References 30 publications
8
178
1
Order By: Relevance
“…Unlike interindividual interactions, intergroup interactions tend to be characterized by greed and fear (Hoyle, Pinkley, & Insko, 1989;Insko, Schopler, Hoyle, Dardis, & Graetz, 1990).…”
Section: Group Morality 8 Interdependence Theory and Noncorrespondencementioning
confidence: 99%
“…Unlike interindividual interactions, intergroup interactions tend to be characterized by greed and fear (Hoyle, Pinkley, & Insko, 1989;Insko, Schopler, Hoyle, Dardis, & Graetz, 1990).…”
Section: Group Morality 8 Interdependence Theory and Noncorrespondencementioning
confidence: 99%
“…Recent papers in economics include Shupp and Williams (2008), Baker, Laury and Williams (2008) and Masclet, Colombier, Denant-Boemont and Loheac (2009). Groups' attitudes towards cooperation and reciprocity were first examined in the context of prisoner's dilemma games: see Pylyshyn, Agnew and Illingworth (1966), Wolosin, Sherman and Maynatt (1975), Lindskold, McElwain and Wayner (1977), Rabbie (1982), Insko, Schopler, Hoyle, Dardis and Graetz (1990), and Schopler and Insko (1992). Wildschut, Pinter, Vevea, Insko and Schopler (2003) provide a meta-analysis of the subject, while Charness, Rigotti and Rustichini (2007) is a more recent contribution in economics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, stigmatized groups may be viewed as out-groups. Research has shown that there is inherent competition between groups resulting in a distrust of the out-group and a need to protect the in-group (Brewer, 2001;Fiske & Ruscher, 1993;Insko, Schopler, Hoyle, Dardis, & Graetz, 1990) Therefore, the stigma of AIDS likely creates an outgroup that diminishes trust even though a logical connection between having AIDS and untrustworthiness is not present. The added factor of homosexual identity likely further contributes to the outgroup status, especially among homophobic individuals.…”
Section: Discussionmentioning
confidence: 99%